Identifikasi Kontaminasi Air Tanah Oleh Polutan Cl- di Kawasan Pertanian Garam, Kecamatan Pademawu, Pamekasan, Madura Menggunakan Metode Geolistrik Tahanan Jenis - Gemilang, Wisnu Arya; Wisha, Ulung Jantama; Kusumah, Gunardi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2019)
ABSTRACTPademawu Sub-District consist of salt ponds reached 740.96 Ha that is the second largest area in Pamekasan. Land-use overlapping problems between salt ponds and settlement influence the environmental degradation enhancement. The presence of salt ponds is indicated as the cause of increased salinity in well-water around the settlement so that the well-water is salty. To determine the influence of salt pond on groundwater pollution, the information regarding surface characteristics as well as the profile beneath the surface is essential. The method consisted of a hydro-geology survey, hydrochemistry, and geophysics (Geo-Electricity method). The type of groundwater is predominated by chloride (Na-Cl) and carbonate (Na-HCO3, Ca-HCO3). Based on groundwater chemistry element calculation, it is observed that there is an influence of salt pond infiltration on groundwater aquifer. The conductivity of groundwater ranged from 15,000Ã¢â‚¬â€œ50,000 Ã‚ÂµS/cm (categorized into salty water). The specific resistance value of rocks beneath the surface varied between 0.1Ã¢â‚¬â€œ300 that is usual in either coastal or alluvial area. The low value of specific resistance associated with alluvial lithology consisted of either brackish water or salt water expected the result of salt pond filtration. The depth of surface saltwater contaminating the aquifer layer ranged from 5 up to 30 meters. The presence of salt ponds influences the level of contamination of Cl- pollutant in shallow groundwater in Pademawu Sub-District, Madura, so it is necessary to re-arrange the land-use system in the coastal area.Keyword: groundwater pollution, salt pond, Pademawu Sub-District, Specific resistance Geo-ElectricityABSTRAKÃ‚Â Kecamatan Pademawu terdiri atas kawasan tambak garam seluas 740,96Ã‚Â Ha yang merupakan wilayah terluas kedua di Pamekasan. Pemasalahan tumpang tindih jenis pemanfaatan lahan tambak garam dengan lahan pemukiman berpengaruh terhadap peningkatan degradasi lingkungan. Keberadaan tambak garam diindikasikan sebagai penyebab meningkatnya kadar salinitas pada air sumur di sekitar pemukiman sehingga air sumur terasa asin. Untuk mengetahui pengaruh keberadaan tambak garam terhadap pencemaran air tanah, dibutuhkan informasi mengenai karakteristik permukaan maupun profil bawah permukaan. Metode penelitian yang dipakai terdiri atas survei hidrogeologi, hidrokimia dan geofisika (metodeÃ‚Â geolistrik). Tipe air tanah didominasi oleh tipe klorida (Na-Cl) dan karbonat (Na-HCO3,Ca-HCO3), hasil perhitungan rasio unsur kimia air tanah menunjukkan adanya pengaruh infiltrasi air tambak garam kedalam akuifer air tanah. Nilai DHL air tanah daerah penelitian didominasi nilai dengan kisaran 15.000Ã¢â‚¬â€œ50.000 Ã‚ÂµS/cm dan masuk dalam sifat air asin. Nilai tahanan jenis batuan bawah permukaan bervariasi antara 0,1Ã¢â‚¬â€œ300 ÃŽÂ©m yang umum dimiliki pada kawasan pesisir atau alluvial. Nilai tahanan jenis rendah berasosiasi dengan litologi alluvial yang terdiri atas air payau atau air asin yang diduga hasil infiltrasi dari air tambak garam. Kedalaman muka air asin yang mencemari lapisan akuifer berada pada kisaran kedalaman 5 hingga 30Ã‚Â m. Keberadaan tambak garam memberi pengaruh terhadap tingkat pencemaran polutan Cl-Ã‚Â pada air tanah dangkal yang ada di Kecamatan Pademawu, Madura, sehingga dibutuhkan penataan ulang sistem tataÃ‚Â guna lahan di kawasan pesisir tersebut.Kata kunci:Ã‚Â pencemaran air tanah, tambak garam, Kecamatan Pademawu, Geolistrik tahanan jenis